2019
DOI: 10.1186/s13071-019-3690-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety of an extended-release injectable moxidectin suspension formulation (ProHeart® 12) in dogs

Abstract: Background The safety of ProHeart® 12 (PH 12; extended-release injectable suspension; 10% moxidectin in glyceryl tristearate microspheres) was evaluated in four studies using Beagle dogs and one study using ivermectin-sensitive Collies. The recommended dose is 0.5 mg/kg subcutaneously once yearly. Methods Study 1: safety margin was evaluated as 3 treatments of PH 12 (0× (control); 1× (recommended dose); 3× (3 times recommended dose) and 5× (5 times recommended dose) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Treatment-related adverse effects were not reported by dog owners or treating veterinarians, and hematologic and biochemical parameters were maintained within reference ranges throughout the treatment. Results of previous studies have shown that administration of up to 5× the label dose of 0.5 mg/ kg of extended-release injectable moxidectin suspension, administered every six months for three consecutive treatments, was well tolerated [22]. Additional studies should be conducted to establish safety of the combined protocol with moxidectin plus doxycycline; however, from a clinical perspective, the treatment protocol followed in this study was shown to be effective and well tolerated in these pet dogs with naturally occurring heartworm infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment-related adverse effects were not reported by dog owners or treating veterinarians, and hematologic and biochemical parameters were maintained within reference ranges throughout the treatment. Results of previous studies have shown that administration of up to 5× the label dose of 0.5 mg/ kg of extended-release injectable moxidectin suspension, administered every six months for three consecutive treatments, was well tolerated [22]. Additional studies should be conducted to establish safety of the combined protocol with moxidectin plus doxycycline; however, from a clinical perspective, the treatment protocol followed in this study was shown to be effective and well tolerated in these pet dogs with naturally occurring heartworm infections.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study of the same extended-release moxidectin suspension in dogs experimentally infected with D. immitis , microfilaremia decreased rapidly, with an average reduction of 20.9% one day after treatment and 96.9% on day 84, although this study used a ML-resistant strain [ 17 ]. In a study conducted as part of the pivotal safety evaluation of ProHeart ® 12, a 3× dose (1.5 mg/kg) demonstrated a > 99% reduction in geometric mean microfilaria counts on day 15 post-treatment against a susceptible strain of heartworm [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive pharmacovigilance monitoring program and post-marketing surveillance showed allergic reactions of 1.26 per 10,000, with a similar rate (1.19) for non-allergic reactions ( 75 ). Recent studies of 12-month SR moxidectin demonstrated safety and efficacy as a preventive ( 64 , 76 ). Reports of adverse events over an extended period were comparable to those reported for ivermectin/pyrantel (Heartgard® Plus, Boehringer Ingelheim) ( 64 ).…”
Section: Efficacy Of Non-arsenical Adulticide Protocolsmentioning
confidence: 99%
“…This long-term treatment is also called "alternative treatment, " "slow kill, " "soft kill, " "doxy-moxi, " or "moxi-doxy" and is recommended to be used when the arsenical drug is unavailable or when fast kill is contraindicated (2, 7). The injectable moxidectin is an extended-release injectable formulation that can be used in breeding animals and a 5X safety margin has been shown (16).…”
mentioning
confidence: 99%